2007
DOI: 10.1017/s000711450769446x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the uptake and secretion of carotene and xanthophyll carotenoids by Caco-2 intestinal cells

Abstract: Carotenoids have been shown to have potential beneficial effects on human health which has led to an increasing interest in the study of their bioavailability. A Caco-2 cell model, as previously described, was employed to examine the percentage transfer of the carotenoids a-carotene, b-carotene, lycopene, astaxanthin, b-cryptoxanthin, lutein and zeaxanthin through an intact, highly differentiated Caco-2 cell monolayer at a range of different amounts. Our results show that astaxanthin, a carotenoid with powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 35 publications
6
19
0
Order By: Relevance
“…The reported absorption rate of micellized lutein in Caco-2 cells on PS range from 7-41% [28,35,36,37]. In our experiments, the percentage of lutein dose in the cell lysates ranged from 18-36% and in the basolateral medium ranged from 0-10%, values that are similar to those previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…The reported absorption rate of micellized lutein in Caco-2 cells on PS range from 7-41% [28,35,36,37]. In our experiments, the percentage of lutein dose in the cell lysates ranged from 18-36% and in the basolateral medium ranged from 0-10%, values that are similar to those previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…Lin et al (2007) reported a better uptake of lycopene into DU145 prostate cancer cells from FCS-compared to THF-supplemented media. Lipoproteins appear to play an important role in the cellular uptake of carotenoids (During and Harrison 2007;O'Sullivan et al 2007). The involvement of the scavenger receptor class B type I (SR-BI) in carotenoid uptake has been demonstrated (van Bennekum et al 2005;During and Harrison 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For the FCS version, which was prepared according to Lin et al (2007) carotenoid stock aliquots were added to FCS in a tenfold higher concentration than desired, mixed and added to FCS free medium. As a third delivery vehicle, Tween 40 was used as described by O'Sullivan et al (2004O'Sullivan et al ( , 2007. Briefly, aliquots of the THF stock solution were concentrated at room temperature in a Jouan RC 10-10 centrifugal evaporator (Saint Herblain, France) and re-dissolved in identical volumes of Tween 40 (200 mL Tween 40 diluted in 1 L acetone).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations